Alkaline Pretreatment Effect on Sweet Sorghum Bagasse for Bioethanol Production - Yanni Sudiyani Sudiyani; Eka Triwahyuni; . Muryanto; Dian Burhani; Joko Waluyo; Anny Sulaswaty; Haznan Abimanyu Abimanyu (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Lignocellulosic material, which consist mainly of cellulose, hemicelluloses and lignin, are among the most promising renewable feedstock for the production of energy and chemicals. The bagasse residue of sweet sorghum can be use utilized as raw material to alternative energy such as bioethanol. Bioethanol production consist of pretreatment, saccharification, fermentation and purification process. The pretreatment process is of great importance to ethanol yield. In the present study, alkaline pretreatment was conducted using a steam explosion reactor at 1300C with concentrations of NaOH 6, and 10% (kg/L) for 10, and 30 min. For ethanol production separate hydrolysis and fermentation (SHF) and simultaneous saccharification and fermentation (SSF) process were conducted with 30 FPU of Ctec2 and Htec2 enzyme and yeast of Saccharomyces cerevisiae. The results shows that maximum cellulose conversion to total glucose plus xylose were found to be greatest with NaOH 10% for 30 min. Maximum ethanol yield 92.19% and high concentration of ethanol 66.88g/L were obtained at SSF condition after 24 h.